Osseointegration of 3D-printed titanium implants with surface and structure modifications. Issue 10 (October 2022) - Lee, Ui-Lyong; Yun, Seokhwan; Lee, Ho; Cao, Hua-Lian; Woo, Su-Heon; Jeong, Yong-Hoon; Jung, Tae-Gon; Kim, Chul Min; Choung, Pill-Hoon
Abstract: Background: The purpose of this study was to establish a mechanical and histological basis for the development of biocompatible maxillofacial reconstruction implants by combining 3D-printed porous titanium structures and surface treatment. Improved osseointegration of 3D-printed titanium implants for reconstruction of maxillofacial segmental bone defect could be advantageous in not only quick osseointegration into the bone tissue but also in stabilizing the reconstruction. Methods: Various macro-mesh titanium scaffolds were fabricated by 3D-printing. Human mesenchymal stem cells were used for cell attachment and proliferation assays. Osteogenic differentiation was confirmed by quantitative polymerase chain reaction analysis. The osseointegration rate was measured using micro computed tomography imaging and histological analysis. Results: In three dimensional-printed scaffold, globular microparticle shape was observed regardless of structure or surface modification. Cell attachment and proliferation rates increased according to the internal mesh structure and surface modification. However, osteogenic differentiation in vitro and osseointegration in vivo revealed that non-mesh structure/non-surface modified scaffolds showed the most appropriate treatment effect. Conclusion: 3D-printed solid structure is the most suitable option for maxillofacial reconstruction. Various mesh structures reduced osteogenesis of the mesenchymal stem cells and osseointegration compared with that by the solid structure. Surface modification by microarc oxidation induced cell proliferation and increased the expression of some osteogenic genes partially; however, most of the markers revealed that the non-anodized solid scaffold was the most suitable for maxillofacial reconstruction. Graphical Abstract: ga1 Highlights: Cellular responses and osseointegration of anodized 3D printed titanium implants with various mesh structures were compared. Anodization may inhibit osteoclastogenesis. Non-anodized solid scaffold was most suitable for maxillofacial reconstruction in terms of osseointegration.